Imaging properties of kinoform Fibonacci lenses - Ferrando, V. (2014)
In this paper, we present a new kind of bifocal kinoform lenses in which the phase distribution is based on the Fibonacci sequence. The focusing properties of these DOEs coined Kinoform Fibonacci lenses (KFLs) are analytically studied and compared with binary-phase Fibonacci lenses (FLs). It is shown that, under monochromatic illumination, a KFL drives most of the incoming light into two single foci, improving in this way the efficiency of the FLs. We have also implemented these lenses with a spatial light modulator. The first images obtained with this type of lenses are presented and evaluated.